1995
DOI: 10.1002/ccd.1810350207
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery fistulas in adults: Incidence, angiographic characteristics, natural history

Abstract: The incidence, angiographic characteristics, and natural history of coronary artery fistulas in patients undergoing diagnostic cardiac catheterization have not been well defined. Of 33,600 patients who had diagnostic cardiac catheterization, 34 (0.1%) had coronary artery fistula. Nineteen fistulas originated from the right, 11 from the left anterior descending, and 4 from the circumflex coronary arteries, respectively. The mean ratio of pulmonary to systemic flow was 1.19 +/- 0.33. Only one patient with coexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
230
3
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(245 citation statements)
references
References 11 publications
3
230
3
4
Order By: Relevance
“…Both coronary arteries are involved in about 5% of cases [1][2][3]. However none of the case in our series had both coronary artery involvement.Levin et al in their review of 363 cases concluded that coronary fistulas have slight right side predominance compared to left.Bilateral fistulas are unique in their tendency to terminate in the pulmonary artery and 17% of the unilateral fistulas drained into the pulmonary artery.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Both coronary arteries are involved in about 5% of cases [1][2][3]. However none of the case in our series had both coronary artery involvement.Levin et al in their review of 363 cases concluded that coronary fistulas have slight right side predominance compared to left.Bilateral fistulas are unique in their tendency to terminate in the pulmonary artery and 17% of the unilateral fistulas drained into the pulmonary artery.…”
Section: Discussionmentioning
confidence: 68%
“…It is defined as an abnormal communication between an epicardial coronary artery and a cardiac chamber, any major vessel or with other vascular structure like coronary sinus or mediastinal vessels. [1][2][3] This anomalous connection was first described in 1865 by Krause [4], but ever since has been reported more frequently with advancement in our imaging modalities and angiographic procedures. It has been classified as a major coronary anomaly under Ogden's classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of coronary-to-cardiac chamber drainage (coronary-cameral fistula, CCF) was reported in 0.08-0.3% of patients who had undergone either elective or emergency diagnostic coronary angiography. 1,2 Most common anomalous fistulas were described as a drainage from the right coronary artery to the right heart chambers, while only a small percentage are linked to the drainage in the left ventricle. 3,4 In contrast to large CCF fistulae, which may have a noticeable communication, small fistulas, named "minimae cordis veneae" or the Thebesius venous system, drain into the heart chambers, forming a vascular network in the cardiac lumen.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 33,600 coronary angiograms in a general population, only 34 (0.1%) were observed, with a good prognosis. 1 Surgical septal myomectomy may also result in a ventricular septal defect (perimembranous-like ventricular septal defect). In such case, the color flow pattern will be seen between the LVOT and the right ventricle in the mid-esophageal long-axis view.…”
mentioning
confidence: 99%